2020
DOI: 10.3389/fgene.2020.586098
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ginger (Zingiber officinale Roscoe) Reference Genes for Gene Expression Analysis

Abstract: Quantitative real-time PCR (qRT-PCR) is widely used in the detection of gene expression level. However, there is no suitable ginger reference gene for qPCR analysis. Therefore, it is the primary task to select and validate the appropriate ginger reference gene to normalize the expression of target genes. In this study, 14 candidate reference genes were selected and analyzed in different tissues (leaf, and rhizome), different development stages, different varieties, and abiotic stress (ABA and salt stress). Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…Due to the use of different algorithms, the results of reference gene stability did not agree with each other. Similar differences have been reported in earlier studies ( Jia et al, 2019 ; Lv et al, 2020 ; Yang et al, 2021 ). Thus, RefFinder was used to ensure the accuracy of the screening results by integrating these results of the above-mentioned four algorithms, and comprehensively evaluating the reference genes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Due to the use of different algorithms, the results of reference gene stability did not agree with each other. Similar differences have been reported in earlier studies ( Jia et al, 2019 ; Lv et al, 2020 ; Yang et al, 2021 ). Thus, RefFinder was used to ensure the accuracy of the screening results by integrating these results of the above-mentioned four algorithms, and comprehensively evaluating the reference genes.…”
Section: Discussionsupporting
confidence: 92%
“…We usually need to introduce reference genes to correct and normalize the expression of target genes. Due to the spatio-temporal specificity of gene expression, a suitable reference gene should be stably and effectively expressed under specific experimental conditions ( Lv et al, 2020 ; Wang G. et al, 2020 ). Therefore, screening appropriate reference genes for specific experimental materials or experimental conditions is important for RT-qPCR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 11 genes that are generally applied as candidate reference genes for numerous plant species were assessed. However, the outcomes of reference gene selection are not constant in various species [ 11 , 37 ], tissues [ 38 , 39 ], and abiotic stress environments [ 14 , 27 ]. For example, our results suggested that UBQ10 was the most unstable in cold-treated stems, while excellent stability was determined in salt-treated leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, increasing studies have revealed that the expression levels of these generally employed reference genes may differ under experimental environments or in various tissues and are generally applicable to specific plant species [ 11 13 ]. Moreover, the current research usually selects reference genes reported in model plants for gene expression analysis because of the lack of genome information regarding non-model plants [ 14 ]. Nevertheless, the stability of reference genes requires further verification because using the inappropriate reference gene will cause errors in the description of the expression level of the target gene [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes, including TUB2 and ACT11 , have been used as the internal reference genes in RT-qPCR analysis ( Li et al, 2020 ). Based on previous reports, Lv et al (2020) selected 14 candidate reference genes and identified 28S and COX as the most stable reference genes in ginger. These 14 candidate reference genes were orthologs of the most commonly used reference genes in other plants, such as a guar ( Jaiswal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%